Предмет:
МатематикаАвтор:
анонимРаскроем скобки и найдем значение выражения:
1) (-3) * (15 + 11) = -3 * 15 - 3 * 11 = -45 - 33 = -78;
2) 6 * (7 - 15) = 6 * 7 - 6 * 15 = 42 - 90 = -48;
3) (-5) * (4 + 12 - 10) = -5 * 4 - 5 * 12 - 5 * (-10) = -20 - 60 + 50 = -30;
4) (-5) * (-4 - 20) = -5 * (-4) - 5 * (-20) = 20 + 100 = 120;
5) (-6) * (-9 + 5) = -6 * (-9) - 6 * 5 = 54 - 30 = 24;
6) (7 - 2 - 10) * (-11) = 7 * (-11) - 2 * (-11) - 10 * (-11) = -77 + 22 + 110 = 55;
7) (7 - 9) * (-8) = 7 * (-8) - 9 * (-8) = -56 + 72 = 16;
8) (-7) * (-5 - 6) = 35 + 42 = 77;
9) (-8 + 2) * (-6) = 48 - 12 = 36.
Автор:
kent54Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть